2020
DOI: 10.33899/csmj.2020.164686
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Bank Loan Risks Using Machine Learning Algorithms

Abstract: Bank loans play a crucial role in the development of banks investment business. Nowadays, there are many risk-related issues associated with bank loans. With the advent of computerization systems, banks have become able to register borrowers' data according their criteria. In fact, there is a tremendous amount of borrowers' data, which makes the process of load management a challenging task. Many studies have utilized data mining algorithms for the purpose of loans classification in terms of repayment or when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…XGBoost is eXtreme Gradient Boosting. It was designed by Chen Tianqi, which is also an improved algorithm for gradient boosting [24]. It improves the loss function.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…XGBoost is eXtreme Gradient Boosting. It was designed by Chen Tianqi, which is also an improved algorithm for gradient boosting [24]. It improves the loss function.…”
Section: Methodsmentioning
confidence: 99%
“…Causes a conditional offset problem. CatBoost improves the statistics and introduces the prior distribution item and its corresponding weight on the original basis, reducing the impact of variables with fewer categories in the classification variables on the data; secondly, it can effectively reduce noise [24]. Another improvement of CatBoost is improving the traditional gradient estimation method to an ordered boosting method, which will obtain an unbiased gradient estimation, reduce the gradient estimation error, reduce the over-fitting problem, and finally improve the model generalization [31,32].…”
Section: Methodsmentioning
confidence: 99%
“…This research carries significant implications for enhancing the risk assessment and sustainability of online lending platforms. In (Alsaleem & Hasoon, 2020), the research objective was to assess the performance of various machine learning algorithms in classifying bank loan risks. With the increasing importance of bank loans and the challenges posed by the abundance of borrower data, this research aimed to aid banks in making informed grant decisions.…”
Section: Related Workmentioning
confidence: 99%
“…Notably, they observed that multilayer perceptron (MLP) outperformed the random forest, naive Bayes (NB), and DTJ48 algorithms in categorizing bank loan risks. The evaluation of the model's performance was conducted using traditional metrics on a dataset comprising 1000 loans and their corresponding repayment status [11].…”
Section: Related Researchmentioning
confidence: 99%